CURCUMINOID AND TOXICITY LEVELS OF ETHANOL EXTRACT OF JAVANESE GINGER (Curcuma xanthorriza) ON BRINE SHRIMP (Artemia salina) LARVAE AND ZEBRAFISH (Danio rerio) EMBRYOS - Syahbirin, Gustini; Mumuh, Nurfadilawati; Mohamad, Kusdiantoro (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was aimed at determining the levels of curcuminoids and analyzing the toxicity of ethanol extracts of Javanese ginger. Methods: Curcuminoid levels were determined using high-performance liquid chromatography, while the toxicity tests were done on larva of brineÂ shrimp (Artemia salina) by using a brine shrimp lethality test (BSLT) method and embryos of zebrafish (Danio rerio) using a zebrafish embryo acuteÂ toxicity (ZFET) method. Â Results: The level curcuminoid of ethanol extracts was 10.5% dry wt., consisting of curcumin at the highest percentage (68.06%) followed by desmethoxycurcumin (24.6%) and bisdemethoxycurcumin (1.41%). In BSLT method, the lethal concentration 50% values (LC) value of our ethanolÂ extract was 238 ppm, whereas in ZFET method, the LCÂ value at 96 hours after fertilization was 80 ppm. The ethanol extract of ginger caused majorÂ malformations of the pericardial edema of zebrafish embryos at a concentration of 100 ppm.Â 50 Conclusion: The ethanol extract of Curcuma xanthorrhiza from Bogor contained curcuminoids consisting of curcumin, desmethoxycurcumin, andÂ bisdemethoxycurcumin, with acute toxicity, caused major malformations on the pericardial edema in zebrafish embryos. Keywords: Curcuma xanthorrhiza, Curcuminoid, Toxicity, Zebrafish embryo acute toxicity.50